Efektivitas Pemberian Salep VCO (Virgin Coconut Oil) Terhadap Penyembuhan Luka Diabetes Melitus di Desa Majasari Bukateja Purbalingga - Ayu Safitri; Dwi Astuti; Fida Dyah Puspasari (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Diabetic wounds are wounds with nerve, blood vessel, and infection abnormalities that continue to get worse and can even be amputated if the infection is not treated properly. Diabetic wounds or foot ulcers are a common complication of diabetics and action must be taken on diabetes mellitus wounds to minimize tissue damage. The action taken is wound care using VCO ointment with the right treatment method, namely the moist/modern dressing technique. Objective : To describe the effectiveness of VCO ointment on wound healing diabetes mellitus. Method : The Case study using descriptive method. Result : In this case study tissue damage improved from 3 to 4 during 15 days of treatment every 3 days, judging by the necrotic/dead tissue being replaced by new/granulating tissue. Conclusion : VCO ointment is effective in helping the healing process in diabetic wound care. Â